Comparative Approach to the Application of Tires for Two-Wheeled Vehicles (International Journal of Food and Nutritional Sciences, 2022)
Tires are the most important component of any vehicle; the mobility of the two-wheeler is determined by the motion of the wheels. Tires are generally comprised of rubber, and the composition of the rubber keeps it soft, therefore new tires with various compositions are utilized nowadays. Much research is carried out using various design tools for different tire materials, but the readily applicable research is limited, hence this research on the actual vehicle is required to understand how tires operate. The study is carried out to assess the qualities of tube tires and tubeless tires based on real-world testing in various places and roads as actual two-wheeler riding is carried out to evaluate their performance. As a result, utilizing a tubeless tire is the most effective and cost-effective option for a bike rider. The usage of tubeless tires is expanding because they have additional advantages, among which is that they are less likely to puncture. As various sorts of studies are to be conducted, tubeless tires will be utilized in most cars in the next years, and the advanced material tube will be produced to minimize punctures in tube tires.